The Theoretical Model of Smart Governance in Local Government - Martinaitis, Tomas (Politologija, 2024)
This article presents the theoretical model of smart governance in local government. It discusses academical discurse of theme and problems related with the fragmentation and over elaborative concentration to technologies of topic. Article analysis the complexity of the term smart and what does smart social system means. It also covers the complexity of the concept smart governance together with its dimensions and posibilities to aquire them to research smart governance in local government. This allows better to understand the term smart governance. Afterwards, a critical view towards national smart governance model is presented and new theoretical framework for research of smart local governance together with its dimensions and attributes in academical discurse are presented. It enables the research smart local governance in Lithuania and abroad.
Keywords: smart; smart social system; smart governance; smart local governance; local government